2016
DOI: 10.1038/ejcn.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Clinical onset of celiac disease after duodenal switch: a case report

Abstract: To our knowledge, this is the first reported case of clinical onset of celiac disease (CD) following duodenal switch surgery. A 61-year-old obese woman developed severe diarrhea soon after bariatric surgery (BS), which was unresponsive to standard medical treatment. After the most common diarrhea etiologies in the immediate postoperative period have been excluded, serological tests were performed. Final diagnosis was determined by anti-tissue transglutaminase antibody positivity. In light of this case report, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…No large-scale studies so far have investigated bariatric surgery in this patient population and there is a paucity of data regarding the impact of bariatric surgery on the outcomes of obese patients with celiac disease. Moreover, there are some case reports suggesting that patients may develop gluten intolerance or even celiac disease after the bariatric procedure, raising questions and concerns about the true benefits of this procedure [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…No large-scale studies so far have investigated bariatric surgery in this patient population and there is a paucity of data regarding the impact of bariatric surgery on the outcomes of obese patients with celiac disease. Moreover, there are some case reports suggesting that patients may develop gluten intolerance or even celiac disease after the bariatric procedure, raising questions and concerns about the true benefits of this procedure [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Four case reports 10-12,16 outlined patients experiencing either nausea, vomiting, diarrhea, and, in 1 instance, 10 mental status fluctuations and eventual death following bariatric surgery (Table 2). In all cases, post-operative biopsies demonstrated jejunal villous atrophy and crypt hyperplasia, and a diagnosis of CD 11,12,16 or subclinical CD 10 were made. Marini et al, 11 Owen et al, 12 and Pané et al 16 reported symptom alleviation following implementation of a GFD.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with a post-operative CD diagnosis, persistent diarrhea, vomiting, malodorous stools, clinically severe weight loss, abdominal pain, and hospitalization occurred. [10][11][12]16 Although these patients returned to near or fully asymptomatic levels following their post-operative diagnosis and introduction of a GFD, they experienced a myriad of additional symptoms than those with a pre-operative CD diagnosis. Comparatively, patients with pre-operative CD diagnoses appeared to have unremarkable post-operative courses following either RYGB or SG.…”
Section: Discussionmentioning
confidence: 99%
“…Final diagnosis was later made based on anti-transglutaminase antibodies. The authors suggest that CD should be ruled out in patients with typical or atypical symptoms after BS regardless of the latency of onset [46]. Another asymptomatic case reported after vertical banded gastroplasty was due to familial history [44].…”
Section: Is There Increased Incidence Of CD After Bariatric Surgery?mentioning
confidence: 98%